Baghdād : From Its Beginnings to the 14th Century - Scheiner, Jens; Toral, Isabel (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2022)
Baghdād: From its Beginnings to the 14th Century offers an exhaustive handbook that covers all possible themes connected to the history of this urban complex in Iraq, from its origins rooted in late antique Mesopotamia up to the aftermath of the Mongol invasion in 1258. Against the common perception of a city founded 762 in a vacuum, which, after experiencing a heyday in a mythical "golden age" under the early ʿAbbāsids, entered since 900 a long period of decline that ended with a complete collapse by savage people from the East in 1258, the volume emphasizes the continuity of Baghdād's urban life, and shows how it was marked by its destiny as caliphal seat and cultural hub. Contributors Mehmetcan Akpınar, Nuha Alshaar, Pavel Basharin, David Bennett, Michal Biran, Richard W. Bulliet, Kirill Dmitriev, Desmond Durkin-Meisterernst, Hend Gilli-Elewy, Beatrice Gruendler, Sebastian Günther, Olof Heilo, Damien Janos, Christopher Melchert, Michael Morony, Bernard O'Kane, Klaus Oschema, Letizia Osti, Parvaneh Pourshariati, Vanessa van Renterghem, Jens Scheiner, Angela Schottenhammer, Y. Zvi Stampfer, Johannes Thomann, Isabel Toral.